2016
DOI: 10.3390/agronomy6010013
|View full text |Cite
|
Sign up to set email alerts
|

Application of Two Bioenergy Byproducts with Contrasting Carbon Availability to a Prairie Soil: Three-Year Crop Response and Changes in Soil Biological and Chemical Properties

Abstract: Abstract:The bioenergy industry produces a wide range of byproducts varying in their chemical composition depending on type of technology employed. In particular, pyrolysis and transesterification conversion processes generate C-rich byproducts of biochar (BC) and glycerol (GL), respectively, which can be added to soil. These two byproducts vary in their carbon availability, and comparing their effects when added to agricultural soil deserves attention. This study investigated the immediate and residual effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…Alburquerque et al (2013) [14] found decrease in or no effect on total plant biomass in response to wheat straw and olive tree pruning BCs produced at low temperature and applied alone under growth chamber conditions. Oat hulls BC produced at 450 • C showed also a limited effect on crop yield under field conditions [16]. In contrast to the results of the current study, other studies, however, reported increases in yield when BC was applied alone [9][10][11][12]15].…”
Section: Wheat Growth Response To Date Palm Residue Biochar Additioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Alburquerque et al (2013) [14] found decrease in or no effect on total plant biomass in response to wheat straw and olive tree pruning BCs produced at low temperature and applied alone under growth chamber conditions. Oat hulls BC produced at 450 • C showed also a limited effect on crop yield under field conditions [16]. In contrast to the results of the current study, other studies, however, reported increases in yield when BC was applied alone [9][10][11][12]15].…”
Section: Wheat Growth Response To Date Palm Residue Biochar Additioncontrasting
confidence: 99%
“…In a recent review, it was reported that the fertilizing value of BC and its nutrient availability, especially N and P, decrease with increasing pyrolysis temperature [5]. Therefore, the effect of BC on crop yield and plant nutrition was found to be variable, and its use as a sole amendment was not always effective, having its supplementation with mineral fertilizers sometimes necessary to promote crop growth [8][9][10][11][12][13][14][15][16]. Some studies found BC to be the most effective when it is applied with mineral fertilizers [8,14,[17][18][19].…”
mentioning
confidence: 99%
“…Since glycerol is a highly labile hydrocarbon, adding glycerol alone or in combination with N immediately increased MBC and MBN in both soils (Figures 3–6), supporting our first hypothesis that adding glycerol to soils will increase MB, but the increase and length of effect may vary between the soils (as discussed in Section 4.2). Similarly, other lab‐based and field studies show MB increases when soils are amended with glycerol (Alotaibi & Schoenau, 2011, 2016; Redmile‐Gordon et al, 2014), other carbohydrates (Recous et al, 1990; Sparling et al, 1981; Wesselsperelo et al, 2006), oily food wastes (Plante & Voroney, 1998; Rashid & Voroney, 2003) and plant residues (Baldwin‐Kordick et al, ; Koranda et al, 2014; Li et al, 2020). In the Clarion soil, MBC declined by 98 days, but moderate (+468C) and high (+1872C) rates of glycerol still had positive effects on MBC across N rates (Figure 3).…”
Section: Discussionmentioning
confidence: 62%
“…This is important, so that P released from biochar does not become a continuous source to downstream water bodies, adding to water pollution. In addition, following meta-analysis should also examine the effect of treated biochars due to research suggesting that activation 59 , composting 53,6063 and joint-application with urea 64 show positive effects on nutrient availability in biochar-amended soils. Finally, this present meta-analysis suggests that the application of biochar to agriculture soils appears to be a reasonable tool in an increasingly P-finite agricultural industry.…”
Section: Discussionmentioning
confidence: 99%